Hypoxia as a stimulus for tissue formation: the concept of organogenesis in microsurgically vascularized tissue engineering constructs - Eweida, Ahmad; Sandberg, Elli; Ritthaler, Oliver; Fleckenstein, Jens; Abo-Madyan, Yasser; Giordano, Frank Anton; Schulte, Matthias; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of cranio-maxillofacial surgery, 2024)
Axial vascularization of tissue constructs is essential to maintain an adequate blood supply for a stable regeneration of a clinically relevant tissue size. The versatility of the arterio-venous loop (AVL) has been previously shown in various small and large animal models as well as in clinical reports for bone regeneration. We have previously demonstrated the capability of the AVL to induce axial vascularization and to support the nourishment of tissue constructs in small animal models after applying high doses of ionizing radiation comparable to those applied for adjuvant radiotherapy after head and neck cancer. We hypothesize that this robust ability to induce regeneration after irradiation could be related to a state of hypoxia inside the constructs that triggers the HIF1 (hypoxia induced factor 1) - SDF1 (stromal derived factor 1) axis leading to chemotaxis of progenitor cells and induction of tissue regeneration and vascularization. We analyzed the expression of HIF1 and SDF1 via immunofluorescence in axially vascularized bone tissue engineering constructs in Lewis rats 2 and 5 weeks after local irradiation with 9Gy or 15Gy. We also analyzed the expression of various genes for osteogenic differentiation (collagen 1, RUNX, alkaline phosphatase and osteonectin) via real time PCR analysis. The expression of HIF1 and SDF1 was enhanced two weeks after irradiation with 15Gy in comparison to non-irradiated constructs. The expression of osteogenic markers was enhanced at the 5-weeks time point with significant results regarding collagen, alkaline phosphatase and osteonectin. These results indicate that the hypoxia within the AVL constructs together with an enhanced SDF1 expression probably play a role in promoting tissue differentiation. The process of tissue generation triggered by hypoxia in the vicinity of a definite vascular axis with enhanced tissue differentiation over time resembles hereby the well-known concept of organogenesis in fetal life.